(untitled) (Journal of National Institute of Ophthalmology, 2025)
Aim: Cystic hygroma is a congenital malformation of the lymphatic system. Surgical excision is the treatment of choice, but injection of sclerosing agent into the cyst is an alternative procedure. The aim of this study was to report a case with successful outcome with using sclerosing agent intralesional bleomycin injection despite of surgery. Materials and methods: Mr. X; a baby boy hailing from Cumilla with the complaints of right sided facial swelling since birth in the pediatric outpatient department of a tertiary eye hospital in 2018. On basis of clinical examination and radiological imaging he was diagnosed as right sided ptosis due to cystic hygroma involving right eyelid, orbit and hemi facial portion of face. Visual acuity was fixation and following at birth. After neuro surgical evaluation he was treated by applying intralesional Bleomycin injection (.3-.6 mg/Kg) at 6 sessions. Primary size of the lesion was 10.6X7.2cm. In each follow up his size of facial swelling was dramatically reduced with time. After completing six sessions in 2023 his lesion was significantly reduced to (2.5X1cm) and his vision is 6/60 in right eye and 6/6 in left eye. Now he was given to patching therapy to treat the stimulation deprived amblyopia. Results: Excellent result was observed after applying Inj Bleomycin of 6 sessions .The swelling was reduced in size and no significant complication was observed. Conclusion: Intralesional bleomycin injection is effective, safe and useful for the treatment of cystic hygroma with low complication rates. J.Natl.Inst.Ophthalmol. 2023; 6(2):67-72